MULTI-LEVEL MARKETING PARADIGM IN ISLAM - Kamilulloh, Farhan; Ambardi, Prio (Islamic Banking & Economic Law Studies (I-BEST), 2022)
This study aims to find out about MLM (Multi Level Marketing) in Islamic view (Islamic law). This research is qualitative descriptive. This study included literary research to examine the written sources such as scientific journals, book references, literature, encyclopedias, scientific articles, scientific papers and other sources that are relevant and related to the object which is being studied. As for the object of study of this research is form of texts or writings that describe and explain about MLM that be popular in Indonesia. Results of this study is Islamic law permit MLM as long as not contrary with Islamic law. However, if it is contrary with Islamic law, so MLM is forbiden. Islam has principles on the development of business systems that must be free of elements dharar (danger), jahalah (vagueness) and zhulm (detrimental or unfair to one party). The system of bonuses to be fair, do not oppress and do not only benefit the people. Businesses also must be free from the element of gambling, oppression, fraud, unclean, riba (interest), vanity etc. If we want to develop a MLM business, it should be free from those elements above. Therefore, the goods or services are commercialized and ordinances sales must be halal, no haram and doubtful, and not in conflict with the principles of Shari'ah above.